Analisis Pengaruh Pemanfaatan Medan Magnet Extremely Low Frequency (ELF) pada Proses Pengolahan Pengawetan Bahan Baku Makanan - Unwaru, Kevin Cahya Andilla; Agustin, Aulia Wulansari; Adelia, Yesica Listian; Sudarti, Sudarti; Anggraeni, Firdha Kusuma Ayu (Peneliti.net, 2025)
Indonesia is known as an island country that has many types of abundant food, consisting of the agricultural sector, the fisheries sector and the industrial sector. However, foodstuffs are often prone to spoilage due to their nature of being easily contaminated by microorganisms. Some reliable solutions in making food durable and long-lasting are the use of ELF magnetic fields. This research has the aim of analyzing the effect of ELF exposure on several food ingredients. The research method used is the article review type literature study method with a total of 30 articles consisting of scientific journals or relevant research journals. The result of the research that has been done is that ELF magnetic field exposure to several food ingredients has great potential to increase the durability of food ingredients by paying attention to the level of intensity of ELF magnetic field exposure and can maintain the quality of its physical condition during the preservation process.